Stress regulation and incision in borderline personality disorder: a pilot study modeling cutting behavior - Reitz, Sarah; Bohus, Martin; Schmahl, Christian (Journal of personality disorders, 2012)
Emotion dysregulation in Borderline Personality Disorder (BPD) is characterized by high baseline negative intensity, high reactivity, and slow return to baseline. Patients with BPD often engage in self-injurious behavior because it leads to immediate relief of stress levels. We aimed to assess stress regulation as well as the influence of tissue damage on subjective (aversive tension) and objective (heart rate) stress correlates in BPD. In 14 unmedicated patients with BPD and 18 healthy controls, a stress induction was followed by an incision into the forearm conducted by an investigator. For aversive tension, we found elevated baseline levels as well as slower return to baseline in BPD. In controls, incision resulted in a short-term increase of aversive tension, whereas tension and heart rate decreased in the BPD group. Our preliminary results support the hypothesis that tissue damage may play a role in disturbed stress regulation in BPD.